The effects of orphanhood and lack of parental care on child vaccination: analyses of 189 cross-sectional UNICEF Multiple Indicator Cluster Surveys from 82 countries, 2005–2022Research in context - Mira Johri; Mehr Munir; Rose Anne Medeiros; Lumana Shakya; Blaine Damte; Anna Bolgrien (EClinicalMedicine, 2025)
Summary: Background: Children lacking parental protection may tend to miss out on essential services. We investigated whether orphans and children without parental care were at risk of sub-optimal vaccination. Methods: Cross-sectional analyses of 189 UNICEF Multiple Indicator Cluster Surveys from 82 predominantly low- and middle-income countries, conducted from January 1, 2005 to December 31, 2022. We used two-level logistic fixed-effects models with individual community-dwelling children aged 12–59 months nested within MICS sampling cluster to estimate the effects of orphanhood (one or both parents deceased) and lack of parental care (children residing with no biological parents) on missed vaccinations. We report the adjusted odds of being a “zero-dose” child (failure to receive any diphtheria-tetanus-pertussis-containing (DTP) vaccine doses), an under-immunised child (failure to receive three DTP doses), failure to receive any measles-containing vaccine (MCV), and failure to receive all eight basic vaccine doses. Findings: The analysis included 739,506 children of which 20.6% (n = 152,314) were zero-dose, 50.4% (n = 372,568) were under-immunised, 50.3% (n = 372,089) had not received any MCV, and 57.8% (n = 427,558) had not received all 8 basic vaccine doses. Orphans had a consistently higher risk of sub-optimal vaccination. Adjusted odds ratios were similar for all binary outcomes (zero-dose (ORadj 1.59; 95% CI: 1.48–1.71, p < 0.001), no DPT3 (ORadj 1.46; 95% CI: 1.38–1.54, p < 0.001), and no MCV and basic incomplete (ORadj 1.42; 95% CI: 1.34–1.50, p < 0.001 for both)). Children lacking parental care experienced similarly elevated risks of sub-optimal vaccination (p < 0.001 for all outcomes). Interpretation: To better support children at risk and uphold their rights, vaccination programmes should prioritise service delivery to orphans and children lacking parental care. Funding: Eunice Kennedy Shriver National Institute of Child Health and Human Development and the Canadian Institutes for Health Research.